Flypaper Effect pada Dana Alokasi Umum (Dau) dan Pendapatan Asli Daerah (PAD) terhadap Belanja Daerah pada Kabupaten/Kota di Indonesia - Diah Ayu Kusumadewi; Arif Rahman (Jurnal Akuntansi dan Auditing Indonesia, 2007)
The most important objective of decentralization by any means is to empower the regions and therefore the development would spread throughout the nation. However, some researches indicate that although decentralization has been implemented in Indonesia for almost a decade, the regions still strongly depend on the central government financially. This research examine the fly paper effect as one of the indicators of the success of decentralization. By examining all regions in Indonesia, the research try to find out (1) whether the General Allocation Fund and Regionally Original Income influence the regions’ spending; (2) between the General Allocation Fund and the Regionally Original Income, which one has more influence on the regions’ spending; (3) whether there has been a fly paper effect or not; and (4) whether the fly paper effect happened in the regions which have a high Regionally Original Income or in the other way. The important findings of this research indicate that all regions although have high Regionally Original Income, experienced the flypaper effect. Again, this result support the indication that the decentralization has not been successfully implemented in Indonesia.Keywords: DAU, PAD, fly paper effect, otonomi daerah